Cassane‐Type Diterpenoids from the Seeds of Caesalpinia bonduc (L.) Roxb. Issue 9 (16th July 2021) - Cao, Jun; Xu, Yunshao; Lou, Ruohan; Shi, Wei; Chen, Jiali; Gan, Lishe; Lu, Jinjian; Lin, Ligen
Abstract: Ten new cassane‐type diterpenoids were isolated from the seeds of Caesalpinia bonduc (L.) Roxb., including 6 α ‐hydroxycaesalpinin P (1 ), 14‐ epi ‐caesalpinin E1 (2 ), 6‐deacetylcaesalmin Z (3 ), 14‐ epi ‐caesalmin Z (4 ), caesalpinolides I (5 ), K (6 ), L (7 ), M (9 ) and N (10 ), and 14‐ epi ‐neocaesalpin L (8 ). Their planar structures and absolute configurations were fully determined by comprehensive spectroscopic methods, including 2D NMR and electronic circular dichroism spectra. Compounds 1 –4 are tetracyclic cassane diterpenoids possessing a furan ring, and compounds 5 –10 are tetracyclic cassane diterpenoids possessing a fused butenolide moiety. The anti‐inflammatory and cytotoxic activities of the isolates were evaluated, while none of them showed obvious effects. The current study identified ten new cassane‐type diterpenoids from the seeds of C . bonduc (L.) Roxb., which enriched the chemical diversity of the titled herbal medicine. Abstract :